Kontribusi Sektor Keuangan Syariah Terhadap Pertumbuhan Ekonomi di Indonesia - Diniyah, Fellasufah (Jurnal Ilmiah Ekonomi Islam, 2023)
This paper aims to explain the relationship between the contribution of the financial sector which consists of the development of Islamic banks, the development of sukuk, the development of Islamic stocks, and the development of Islamic mutual funds to Indonesia's economic growth. This study uses quarterly time series data for the period between 2013Q1 – 2020Q4 and the analysis model used is the Vector Error Correlation Model (VECM) by carrying out unit root tests, cointegration tests, Granger causality tests, this study also uses the impulse Response Function, and Variance Decomposition. The results of this study indicate that the development of Islamic banking, the development of sukuk, the development of the Islamic stock market, and the development of Islamic mutual funds have a long-term influence on economic growth. while the development of the Islamic Banking and the development of the Islamic stock market have a short-term influence on economic growth. This research is expected to provide an overview of the condition of Islamic finance in Indonesia so that it can become a reference for relevant authorities in formulating or determining future policies for the development of Islamic finance.